Akibat Hukum Perceraian Pada Perkawinan Campuran - I Wayan Ika Suyun Yastika; I Nyoman Putu Budiartha; Ni Made Pupspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2019)
Besides choosing to vacation amid the beauty of the island of Bali, these tourists are sometimes also interested in the beauty of the women on the island of Bali to become partners and do mixed marriages. But in the midst of the large number of mixed marriages that exist in Bali and in the Badung Regency in particular, couples of different nationalities often separate in the middle of their life journey and do not know what effects of divorce on the mixed marriages they lead. From the background above, the author takes the title of the thesis